Stock Market Efficiency Promotes Economic Development: Empirical Evidence from Africa - Dike, Christie (International Journal of Economics and Financial Issues, 2016)
The stock market plays an essential role in the growth of commerce and industry which ultimately affects the economy of the country to a large extent. This is the rationale that the industrial bodies, government advisors and even the central bank of the country keep a close eye on the activities of the stock market. With the ever-growing importance of stock markets, an overwhelming number of studies have been carried out worldwide to investigate the link which exists between stock market development and economic growth. However, most of these studies focused on developed countries. Since studies analyzing this link are scant in the African region, this paper endeavours to scrutinize the relationship between equity market development and economic growth in a sample of African countries. To this end, this paper analyzes the relationship between stock market development, banking development and economic growth in a unified framework using annual panel data for the period 1990-2015, through a dynamic Panel Vector Error Correction Model (PVECM). The results seem to suggest that stock market development plays an important role in generating gains in terms of economic growth. Keywords: Economic growth, Stock market development, Panel VECM, Co integration JEL Classifications: E40, G20, O16, E44, O43